Pengaruh Instagram Dan Facebook Terhadap Keputusan Pembelian Di Toko Sparepart Modifikasi Kaji Lb Desa Kebonagung - Purwadirangga, Septariannas; Rahayu; Hidayat, M. Syamsul (PT. Kreasi Karya Majakata, 2024)
This research examines the influence of Instagram and Facebook on the decision to purchase used clothing at the Kaji Lb modified spare parts shop, Kebonagung Village. The population in this study were all consumers of the Kaji Lb modification spare parts shop. The sampling technique in this research uses the Accidental Sampling technique. Accidental sampling is a technique for determining samples based on chance, so that researchers can take samples from anyone they meet without prior planning. So samples can be found from the period from June to July, there are approximately 100 samples. The data analysis method used in this research is multiple linear regression which is used to determine the influence between the independent variable and the dependent variable, namely between Instagram (X1) and Facebook (X2) on purchasing decisions (Y). By using the SPSS program version 29.0.0. The research results show that Instagram has a significant effect on purchasing decisions with a significance level of <0.001 (<0.05) and Facebook has a significant effect on choosing decisions with a significance level of <0.001 (<0.005).